2004
DOI: 10.1111/j.1445-1433.2004.03187.x
|View full text |Cite
|
Sign up to set email alerts
|

Is bilateral duplex scanning necessary in patients with symptoms of deep venous thrombosis?

Abstract: Overall the diagnostic yield of VDUS was low in this study, with an incidence of 16% of DVT detected in symptomatic patients. Techniques that improve the diagnostic yield of VDUS in symptomatic patients are required. A significant proportion (23%) of the DVT detected in this study were bilateral, and a small but significant proportion (10%) of DVT found in patients presenting with unilateral symptoms were only in the asymptomatic contralateral limb. Our study supports bilateral VDUS in symptomatic inpatients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
3
0
2
Order By: Relevance
“…Unilateral presentation of DVT was encountered more in 87.2% (34/39) comparing favorably with a retrospective study by Lemech et al(2004) that found 69%(n=1029) 12 but differed in the bilateral presentation of the symptoms in 31%(n=1029) unlike in our study where we found only 12.8%(5/39). This could be as a result of the higher number recruited in their study 1029 verses 103 participants and their study only looked at cases with DVT specifically.…”
Section: Sonographic Finding In Relation To Demographics Amongst Femasupporting
confidence: 66%
See 1 more Smart Citation
“…Unilateral presentation of DVT was encountered more in 87.2% (34/39) comparing favorably with a retrospective study by Lemech et al(2004) that found 69%(n=1029) 12 but differed in the bilateral presentation of the symptoms in 31%(n=1029) unlike in our study where we found only 12.8%(5/39). This could be as a result of the higher number recruited in their study 1029 verses 103 participants and their study only looked at cases with DVT specifically.…”
Section: Sonographic Finding In Relation To Demographics Amongst Femasupporting
confidence: 66%
“…In two different studies, it was found that DVT commonly presents as unilateral swelling 12,13 . In these studies, unilateral and bilateral DVT was present in 31%(n =1029) and 5%(n=159) respectively.…”
Section: Introduction:-mentioning
confidence: 99%
“…[1][2][3] Conversely, other authors have advocated the importance of bilateral studies, especially in patients with predisposing risk factors for thrombosis. 4,5 Prior to the development of venous duplex imaging, patients underwent venography, which was typically done as a unilateral study because of its invasive nature. Is it possible to identify which patients should undergo bilateral examinations?…”
mentioning
confidence: 99%
“…However, inpatients with unilateral symptoms were diagnosed with thrombosis on the symptomatic side in 24% of cases, on the asymptomatic limb in only 5%, and on both limbs in 5% of cases 21 . In another study, Lemech et al found about 10% of bilateral DVT in patients with unilateral symptoms, thus suggesting that inpatients should have both limbs investigated 22 .…”
Section: Should Deep Vein Thrombosis Investigation Be Bilateral?mentioning
confidence: 98%